Seismic Performance Enhancement of a Reinforced Concrete Building Using an RB-HDRC Base Isolation System - Nur Khofifah; Ahmad Basshofi Habieb (Universitas Islam Raden Rahmat, Malang, 2026)
This study investigates the seismic performance enhancement of a four-story reinforced concrete building retrofitted with a Rubber Bearing-High Damping Rubber Core (RB-HDRC) base isolation system. A three-dimensional numerical model was developed and subjected to nonlinear time-history analysis under two design earthquake levesl (BSE 1-E and BSE 2-E). The results indicate that the base isolation system significantly reduces seismic demands compared to the fixed-base condition. Peak base shear was reduced by approximately 48% at the BSE-1E level and by 52% at the BSE-2E level. Roof acceleration decreased by about 76% and 79% at the BSE 1-E and BSE 2-E levels, respectively. The maximum interstory drift ratio was also reduced, demonstrating improved deformation control in the isolated system. Furthermore, the number of plastic hinges decreased significantly, while the energy dissipation capacity increased due to the hysteretic behavior of the RB-HDRC isolator. These findings demonstrate that RB-HDRC base isolation effectively enhances structural resilience and represents a promising strategy for improving the seismic performance of reinforced concrete buildings.